2012
DOI: 10.1186/1471-2164-13-382
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing the genome of Marssonina brunnea reveals fungus-poplar co-evolution

Abstract: BackgroundThe fungus Marssonina brunnea is a causal pathogen of Marssonina leaf spot that devastates poplar plantations by defoliating susceptible trees before normal fall leaf drop.ResultsWe sequence the genome of M. brunnea with a size of 52 Mb assembled into 89 scaffolds, representing the first sequenced Dermateaceae genome. By inoculating this fungus onto a poplar hybrid clone, we investigate how M. brunnea interacts and co-evolves with its host to colonize poplar leaves. While a handful of virulence genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 52 publications
(54 reference statements)
0
46
1
Order By: Relevance
“…This pathogen infects poplar leaves via the conidia or ascospores in primary infection and extend throughout the season with the conidia (Ostry, ). As previously reported, the sexual state of M. brunnea was not found in China and New Zealand, and genomic analysis showed that this pathogen might lack the capacity to perform sexual reproduction in China (He & Yang, ; Han, Li, & Huang, ; Zhu et al., ). M. brunnea infects various poplar species (Han, Yin, Li, Huang, & Wu, ; Spiers, ) and has often caused outbreaks in various countries in Europe (Newcombe & Callan, ; Spiers, ).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…This pathogen infects poplar leaves via the conidia or ascospores in primary infection and extend throughout the season with the conidia (Ostry, ). As previously reported, the sexual state of M. brunnea was not found in China and New Zealand, and genomic analysis showed that this pathogen might lack the capacity to perform sexual reproduction in China (He & Yang, ; Han, Li, & Huang, ; Zhu et al., ). M. brunnea infects various poplar species (Han, Yin, Li, Huang, & Wu, ; Spiers, ) and has often caused outbreaks in various countries in Europe (Newcombe & Callan, ; Spiers, ).…”
Section: Introductionmentioning
confidence: 59%
“…Marssonina leaf spot disease of poplar (MLDP) is a major disease affecting poplar trees (Beare, Archer, & Bell, ; He & Yang, ). MLDP generally causes black spots on the surface of the leaves and lesions on the petioles, resulting in premature defoliation and a significant reduction in photosynthesis (Spiers, ; Zhu et al., ). Furthermore, MLDP outbreaks can lead to tree death, which causes significant losses to the poplar industry, with a 30% annual decrease in average wood production having been recorded (Erickson, Stanosz, & Kruger, ; Wu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The total coverage of repetitive sequences is relatively high as compared to other fungi reaching 31% in R. commune , but lower than in the close relative Marssonina brunnea f.sp. ‘multigermtubi’ (see below; 42% [33]).…”
Section: Resultsmentioning
confidence: 99%
“…The closest relative of Rhynchosporium spp., the poplar pathogen M. brunnea f.sp. ‘multigermtubi’ [33], belongs to the Dermataceae , a family of one of the most diverse ascomycete orders, the Helotiales . This confirms a previous ITS-based phylogenetic analysis, which located R. commune and R. orthosporum between the Dermataceae species Tapesia yallundae (syn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation